Acute myeloid leukemia in the vascular niche. Issue 2 (1st October 2016) - Cogle, Christopher R.; Bosse, Raphael C.; Brewer, Takae; Migdady, Yazan; Shirzad, Reza; Kampen, Kim Rosalie; Saki, Najmaldin
Highlights: We review how AML cells are protected and promoted by the vascular niche. We discuss results of vascular targeting agent clinical trials in AML. We provide future perspectives on optimizing anti-vascular agents for AML. Abstract: The greatest challenge in treating acute myeloid leukemia (AML) is refractory disease. With approximately 60–80% of AML patients dying of relapsed disease, there is an urgent need to define and target mechanisms of drug resistance. Unfortunately, targeting cell-intrinsic resistance has failed to improve clinical outcomes in AML. Emerging data show that cell-extrinsic factors in the bone marrow microenvironment protect and support AML cells. The vascular niche, in particular, regulates AML cell survival and cell cycling by both paracrine secretion and adhesive contact with endothelial cells. Moreover, AML cells can functionally integrate within vascular endothelia, undergo quiescence, and resist cytotoxic chemotherapy. Together, these findings support the notion of blood vessels as sanctuary sites for AML. Therefore, vascular targeting agents may serve to remit AML. Several early phase clinical trials have tested anti-angiogenic agents, leukemia mobilizing agents, and vascular disrupting agents in AML patients. In general, these agents can be safely administered to AML patients and cardiovascular side effects were reported. Response rates to vascular targeting agents in AML have been modest; however, a majority of vascular targeting trials in AML are monotherapy in design and indiscriminate in patient recruitment. When considering the chemosensitizing effects of targeting the microenvironment, there is a strong rationale to build upon these early phase clinical trials and initiate phase IB/II trials of combination therapy where vascular targeting agents are positioned as priming agents for cytotoxic chemotherapy.